The procedure for tax control in the Republic of Uzbekistan - Mingboev Umid Akbar (Genius Journals, 2023)
The article deals with the theoretical issues of tax audit. The nature of the tax audit norm included in the new Tax Code of the Republic of Uzbekistan is disclosed. The experience of organizing and conducting tax audits in foreign countries is given.
Keywords: financial control; tax audits; audit